Apakah Strategi Differentation Lebih Unggul Mempengaruhi Kinerja Keuangan Dibandingkan Cost Leadership? - Lucy Margaret; Juniarti Juniarti (Business Accounting Review, 2020)
Strategy is a description of a company in using and managing its resources to achieve the goal of competitive advantage. Therefore, this study aimed to see which strategy is superior and more affects on financial performance of the companies between differentiation and cost leadership strategies in the manufacture industry in Indonesia. Financial performance is measured using return on assets. The object of this research were 134 companies selected using purposive sampling. Data analysis used multiple regression analysis with panel data. This study found that there is a significant relationship between differentiation and firm performance. While, positive and not significant between cost leadership and company performance. This research uses firm size and firm age as control variables.